ROKEYA SAKHAWAT HOSSAIN’S SULTANA’S DREAM: AN AVANT-GARDE OF ECONOMIC INDEPENDENCE OF WOMEN TOWARDS FREEDOM - Mahbubul Alam; Nawshan Ara Rima (Universitas Islam Sumatera Utara (UISU), 2020)
Critics and research scholars, so far have observed and considered Rokeya Sakhawat Hossain’s (1880-1932) Sultana’s Dream to be a feminist utopia- an imaginary place of ideal perfection or any non-existent society described in her considerable detail-overlooking main purpose, to an extent, in writing the novella. When the idea of female emancipation and awakening was completely unknown and unimaginable to Indian women in general, Begum Rokeya tried to instill its zeal in these ignorant women, got them to believe in their power, and showed a way of their ultimate freedom as something real and possible through a dream. The bitter discrimination she experienced in her own family as a girl, and the misfortune of the women of her society and women of undivided India bled her soft heart and urged her to work for the advancement and empowerment of women breaking all the traditional, social, cultural and religious barriers. In this regard, besides quality education, she believed that the first and the most important condition for female emancipation is self-reliance or economic independence where she differed from all other major contemporary feminists of the world for her unequivocal approach. The paper, therefore, aims at exposing the pathetic consequences of deprived and distressed women drowned under the dirt of illiteracy, fanaticism, superstitions, and prejudices showing the way they can be educated, economically solvent, self-reliant towards ultimate freedom and attributed state power and responsibilities which Begum Rokeya presents in the disguise of a dream in Sultana’s Dream.